Growth and gut morphology of diploid and triploid juvenile Atlantic cod (Gadus morhua) - Vargas, Cecilia Campos; Hagen, Ørjan; Solberg, Christel; Jobling, Malcolm; Peruzzi, Stefano (Aquaculture Research, 2014)
Author's accepted version (post-print). This is the peer reviewed version of the following article: Vargas, C.C., Hagen, Ø., Solberg, C., Jobling, M. & Peruzzi, S. (2014). Growth and gut morphology of diploid and triploid juvenile Atlantic cod (Gadus morhua). Aquaculture Research, which has been published in final form at http://dx.doi.org/10.1111/are.12603. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Self-Archiving (http://olabout.wiley.com/WileyCDA/Section/id-820227.html).